Strength Training Improves Metabolic Health Markers in Older Individual Regardless of Training Frequency - Ihalainen, Johanna K.; Inglis, Alistair; Mäkinen, Tuomas; Newton, Robert U.; Kainulainen, Heikki; Kyröläinen, Heikki; Walker, Simon (Frontiers in Physiology, 2019)
The main purpose of the present study was to investigate the effect of frequency, thereby increasing training volume, of resistance training on body composition, inflammation markers, lipid and glycemic profile in healthy older individuals (age range 65-75y). Ninety-two healthy participants were randomly assigned to one of four groups; performing strength training one- (EX1), two- (EX2), or three- (EX3) times-per-week and a non-training control (CON) group. Whole-body strength training was performed using 2–5 sets and 4–12 repetitions per exercise and 7–9 exercises per session. All training groups attended supervised resistance training for 6 months. Body composition was measured by dual X-ray absorptiometry and fasting blood samples were taken pre- and post-training. There were significant main effects of time for total fat mass (F=28.12, P<0.001) and abdominal fat mass (F=20.72, P<0.001). Pre- to post-study, statistically significant reductions in fat mass (Δ=-1.3±1.4kg, P<0.001, n=26) were observed in EX3. Pre- to post-study reductions in low density lipoprotein (LDL) concentration (Δ=-0.38±0.44 mmol·L-1, P=0.003, n=19) were observed only in EX3, whereas a significant pre- to post-study increases in high density lipoprotein (HDL) concentration (0.14-0.19 mmol·L-1) were observed in all training groups. Most variables at baseline demonstrated a significant (negative) relationship when correlating baseline values with their change during the study including: Interleukin-6 (IL-6) (r=-0.583, P<0.001), high-sensitivity c-reactive protein (hs-CRP) (r=-0.471, P<0.001, and systolic blood pressure (r=-0.402, P=0.003). The present study suggests that having more than two resistance training sessions in a week could be of benefit in the management of body composition and lipid profile. Nevertheless, interestingly, and importantly, those individuals with a higher baseline in systolic blood pressure, IL-6 and hs-CRP derived greatest benefit from the resistance training intervention, regardless of how many times-a-week they trained. Finally, the present study found no evidence that higher training frequency would induce greater benefit regarding inflammation markers or glycemic profile in healthy older adults.